Biodiesel dari Minyak Biji Kapuk (Ceiba Pentandra) Menggunakan Katalis Ca/Hydrotalcite - Erlinda Ningsih; Yustia Wulandari Mirzayanti; Achmad Chusnun Niam; Pipit Febrianita; Wanvia Vangesti (Universitas Tribhuwana Tunggadewi Malang, 2019)
The availability of fuel caused by fossil decline, so that required alternative fuel that can fulfill a need consumers.Biodiesel is alternative fuel of seeds having a big to be developed.One of seeds that can be used is seeds kapok.The purpose of this research is to know the influence of ratio molar oil methanol and the addition of a catalyst to yield.Making biodiesel this through four stage that is preparasi a catalyst ca / hydrotalcite, degumming.Esterifikasi and transesterifikasi.Oil the kapok already omitted gum and lowered levels ffa below 1 %, then the oil processed transesterifikasi by the addition of a catalyst already dipreparasi ( 0.5 %, 1 percent and 1.5 % w / w of a mass oil ).Based on the research obtained on ratios molar 1 oil: 20 methanol produce fame highest levels of 5,55 % and yield biodiesel produced is 3,92 %.